IMPLEMENTASI PEMBUATAN PAKAN SAPI BERBASIS LIMBAH PERTANIAN DAN PERKEBUNAN PADA KELOMPOK TERNAK DI KAMPUNG SOTA PERBATASAN REPUBLIK INDONESIA/PAPUA NEW GUINEA - Nurcholis Nurcholis; Lilik Sumaryanti; Jamaludin Jamaludin (Universitas Mataram, 2023)
Sota's potential as a livestock center is good for development, especially for cattle. However, until now agricultural and plantation waste (palm oilcake) has not been used by breeders as a source of good nutritional feed for cattle. Therefore, the aim of this training is to improve the skills of farmers in making fermented feed and pellets for cattle. The method used is interviews, assistance to farmers in the form of training in making fermented feed and pellets. The result of the implementation of cattle feed production is that it is easier for breeders of productive age to understand and carry out the process of making fermented feed and pellets. Farmers prefer fermented feed as fattening feed compared to pelleted feed which is 87.6% versus 12.4%. The results of the feed making training showed that the level of understanding and mastery before and after the training increased. The conclusion in this service is that most community groups are of productive age, and prefer the process of making fermented feed, as well as having a positive impact on improving the skills of breeders.